-143+10x=4x+49

Simple and best practice solution for -143+10x=4x+49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -143+10x=4x+49 equation:


Simplifying
-143 + 10x = 4x + 49

Reorder the terms:
-143 + 10x = 49 + 4x

Solving
-143 + 10x = 49 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-143 + 10x + -4x = 49 + 4x + -4x

Combine like terms: 10x + -4x = 6x
-143 + 6x = 49 + 4x + -4x

Combine like terms: 4x + -4x = 0
-143 + 6x = 49 + 0
-143 + 6x = 49

Add '143' to each side of the equation.
-143 + 143 + 6x = 49 + 143

Combine like terms: -143 + 143 = 0
0 + 6x = 49 + 143
6x = 49 + 143

Combine like terms: 49 + 143 = 192
6x = 192

Divide each side by '6'.
x = 32

Simplifying
x = 32

See similar equations:

| 16d^2=-64d | | x+y+2x+2=39 | | -4(-6x+3)=-3x | | 5x+5x+3=32 | | 11x+7=15x-5 | | 6x^3+3x^3=18x | | x+3*4=9 | | 20x+11=360 | | -138-4x=192+11x | | x(x+3)=35 | | -2.67x-8.4=6.072+0.03x | | y=(-0.25)x+50 | | -230+2x=19+3x | | (t+z)=45z+67 | | g(X)=x-3+2 | | 2d-4=-3 | | 6x-15+4x+8=3x+9+7x-16 | | 3x+20=1500 | | 2g+7=15 | | -11+2x=19+3x | | 24x+11=123 | | -20+13x=22+11x | | 3c+2p=78 | | X-9=-3+8 | | 2b+1=-9 | | 2*-1.6+6y=-12 | | -3(7m+4)=20-5m | | 2p-4=3 | | 3x=(x-56) | | 3x+10x=5x+4x | | 7(6+3x)=105A | | 5y-3=-15 |

Equations solver categories